KELOMPOK DIFABEL DAN KESEMPATAN KERJA: PENANGGULANGAN DISKRIMINASI DI DUNIA KERJA DALAM PERSPEKTIF PEKERJAAN SOSIAL - Anisa Anisa (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2019)
Disability is a state where people experiencing who have not do things in the usual way. Even so, people with disabilities are still a part of society that must earn equal rights. This article aims: 1) to identify the existing condition regarding with the discrimination of diffable gropus in Indonesia, especially when they will participate to inte the workforce, 2) to analyze an effort to overcome public stigma for diffable groups in the work environment through a social work approach. The method of this study used literature study with collecting secondary data from various source. The result of study showed that diffable groups have equal opportunity with all people to obtain jobs and participate in the economic development. Futhermore people with disabilities, government policies, social workers, social services, and public facilities play a crucial role in making it easier for people with disabilities in the workforce. Therefore, the government’s efforts to be responsible for the welfare of all its citizens can be conducted equal access by implementing an inclusive social development program. Inclusive program can also mean that development policies are designed fairly and equitably by involving all communities actively so that all Indonesian citizens can enjoy the results of development.